Conservation of holm oak (Quercus ilex) by in vitro culture - Cernadas, María José; Martínez, María Teresa; Corredoira, Elena; San José, María del Carmen (Mediterranean Botany, 2018)
In vitro culture techniques are used to propagate tree species, as well as to conserve the species in the short and long term. In the present study, in vitro propagation and conservation of holm oak (Quercus ilex L.) were successfully achieved using juvenile material. Mature acorns were germinated under controlled conditions of moisture and temperature, and 3-month-old seedlings were used as source of explants for culture initiation. Micropropagation via axillary bud proliferation was achieved by culturing shoots in a vertical position on Woody Plant Medium containing different cytokinins and/or concentrations, which were changed every 2 weeks over a 6-week multiplication cycle, as follows: 0.1 mg L-1 benzyladenine (BA) for the first 2 weeks, 0.05 mg L-1 BA for the next 2 weeks, and 0.01 mg L-1 BA plus 0.1 mg L-1 zeatin for the last 2 weeks. Acceptable rooting rates were obtained by culturing microcuttings in Murashige & Skoog medium with half-strength macronutrients supplemented with 3 or 5 mg L-1 indole-3-butyric acid (IBA) in combination with 0.1 mg L-1 naphthalene acetic acid (NAA) for 15 days and subsequent transfer to auxin-free medium for 4 weeks.